2020
DOI: 10.1590/0034-7167-2018-0173
|View full text |Cite
|
Sign up to set email alerts
|

Depression among nursing students and its association with academic life

Abstract: Objective: To measure the levels of depression among Nursing students from a public institution of higher education and the association with aspects of academic life. Method: Analytical and quantitative study with 203 students from a higher education institution that uses active methodologies. We used Beck’s Depression Inventory and the Likert type scale of academic factors. Results: We verified that 19.2% had moderate or severe levels of depression. Higher levels of depression were associated with female ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 11 publications
2
8
0
15
Order By: Relevance
“…Anxiety is characterized as an emotional state of self-protection oriented towards the future, with physiological and behavioral responses directed to threatening situations (3)(4) . It becomes pathological when prolonged and disproportionate to the stimulus, and can manifest itself through signs and symptoms such as tachycardia, changes in appetite, insomnia, irritability, sadness, lack of concentration, among others (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is characterized as an emotional state of self-protection oriented towards the future, with physiological and behavioral responses directed to threatening situations (3)(4) . It becomes pathological when prolonged and disproportionate to the stimulus, and can manifest itself through signs and symptoms such as tachycardia, changes in appetite, insomnia, irritability, sadness, lack of concentration, among others (4) .…”
Section: Introductionmentioning
confidence: 99%
“…O quadro de maioria feminina no curso de graduação em Enfermagem é observado em outros locais, como em São José do Rio Preto/SP com 87,88% (Ribeiro, Bragiola, Eid, & Pompeo, 2019), em Brasília/DF com 81,3% (Facioli, Barros, Melo, Ogliari, & Custódio, 2019), em Porto Alegre/RS com 80% (Urbanetto, Rocha, Dutra, Maciel, Bandeira, & Magnago, 2019), em Fortaleza/CE com 94,06% (Cestari, Barbosa, Florêncio, Pessoa, & Moreira, 2017), em Florianópolis/SC com 92,5% (Petry, Padilha, Kuhnen, & Meirelles, 2019), em Vitoria da Conquista/BA com 83,33% (Simoes, Penna, Rodrigues, Carinhanha, Pereira, & Machado, 2019), em Itajubá/MG com 95,45% (Silva, Alves, & Fortes, 2019), em Campo Grande/MS com 85,6% (Eufrazio, Batiston, & Medeiros, 2019) e em Coari/AM com 68,2% (Pereira, Reis, & Oliveira, 2019). Demonstrando que em todo território brasileiro encontram-se predominância de mulheres graduandas de enfermagem.…”
Section: Resultsunclassified
“…Acontecimentos avaliados em outras pesquisas do tema, porém em locais distintos, como em Brasília/DF que a média de idade foi de 22 anos, sendo sua maioria até 20 anos (49,3%) (Facioli et al, 2019), em Fortaleza/CE a idade variou de 18 a 49 anos, mas a faixa etária da maioria dos participantes ficou entre 18 e 29 anos (86,2%) (Cestari et al, 2017), em Florianópolis/SC a idade dos participantes variou de 18 a 37 anos, com faixa etária da maioria de 18 a 23 anos (55%) (Petry et al, 2019), em Itajubá/MG a faixa etária da maioria foi entre 21 a 25 anos (77,27%) (Silva et al, 2019), em Campo Grande/MS obteve a média de idade de 21 anos (Eufrazio et al, 2019), e em Coari/AM a faixa etária da maioria foi de 18 a 23 anos (66,9%) (Pereira et al, 2019). Fatos estes que comprovam que a maioria dos estudantes universitários são jovens e se enquadram nas estatísticas divulgadas nos dados do INEP.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…This study indicated the course as a significant factor for the development of depressive symptoms in university students. In a quantitative and analytical study carried out in a public institution from Brasília with 203 Nursing students and to measure the levels of depressive symptoms among the students, in addition to evaluating their association with academic life factors, Facioli et al (34) evidenced certain depressive predisposition with the course, due to the significant dedication to the workload by the students, in addition to being associated with a limitation of the time available to perform physical and leisure activities.…”
Section: Discussionmentioning
confidence: 99%